Extraction of natural dye from Oroxylumb indicum (L.) Kurz by using different solvents for Thai eri silk dyeing - Sanai, Aritart; Nachai, Thippawan; Merat , Kesorn (Journal of Applied Research on Science and Technology (JARST), 2023)
Among various textile types in Thailand, silk is the largest market share. Thus, upgrading or developing either the dying process or the quality of fabric dried for Thai silk is still necessary. Natural dyes have become an interesting resource because they are more environmentally friendly than synthetic dyes. Thus, this work aims to study the effect of different solvents for dye extraction from Oroxylumb Indicum (L.) Kurz on Eri Thai silk dyeing. Each solvent used for extraction gave a different relative tannic acid and quercetin content. Therefore, this further leads to different properties of dyed fabrics, such as color properties and washing fastness index. From the different solvents studied, the yield of the extracted dyes was on the order of EtOH/water (50: 50) > MeOH/water (50:50) > MeOH EtOH > water. Then, the optimal ratios between EtOH and water in the efficient extraction were varied as follows water, EtOH/water (25: 75), EtOH/water (50: 50), EtOH/water (75:25), and EtOH. The result showed that EtOH/water (50: 50) was still the most effective for dye extraction. In addition, the effect of dose, temperature, and time of Oroxylumb Indicum (L.) Kurz was 8.0 g/L, 60 °C, and 60 min, which were considered optimal extraction conditions due to the high relative contents of tannic acid and quercetin. As a result, the fabric of Eri silk dyed has a high quality of fastness rating. Overall, these results could point out the use of extracted dye from Oroxylumb Indicum (L.) Kurz has the potential as an alternative dye for Eri Thai silk dyeing.